Diagnostic Accuracy of MDCT Coronary Angiography in Patients with Ischemic Heart Disease - Arti Kumari; Suresh Kumar Toppo; Prakash Kumar; Rajeev Kumar Ranjan; Anima R. Xalxo; Nisha Rai; Harsha Kaur (Journal of Pharmacy and Bioallied Sciences)
Introduction: One of the main causes of illness and death in both India and globally is coronary artery disease, or CAD. Previously, the majority of conventional catheter examinations were performed simply for diagnostic purposes. So, a noninvasive and trustworthy method was highly desirable for early CAD detection and coronary artery imaging. Material and Methods: Symptomatic patients attending the routine cardiac outpatient department at RIMS, Ranchi, who were advised to undergo coronary CT angiography (CCTA) for further evaluation in the Department of Radiodiagnosis were included. Results: A total of 101 symptomatic patients were studied for patency of coronary vessels in both CCTA and conventional coronary angiography. Based on the CCTA of the 101 patients, majority of the patients belong to single vessel disease. CCTA revealed 124 lesions, of which 101 were considered serious with a majority of lesions in the left anterior descending. The sensitivity, specificity, positive predictive value, and negative predictive value of the multidetector computed tomography were 98.4, 91.7, 95, and 97.05%. Conclusion: CCTA is a good negative predictive value technique for coronary stenosis and is relatively trustworthy.